Turner sendromlu olgularda osteoporoz sıklığı ve östrojen takviye tedavisi için optimal başlama yaşının tespiti - Koçkar, Tuba; Ugan Atik, Sezen; Gürsoy, Semra; Özgen, İlker Tolga; Barut, Yüksel; Adal, Servet Erdal (Kare Yayıncılık, 2017)
Amaç: Turner Sendromunda boy kısalığı ve gonadal yetmezliğe bağlı hipogonadizm en sık karşılaşılan durumlardır. Ovaryan yetmezlik nedeni ile östrojen takviye tedavisi alması gereken bu olgularda, östrojen için uygun dozun belirlenmesi ve östrojen takviyesinin zamanlaması önem taşımaktadır. Bu çalışmada amacımız, Turner sendromlu olgularda, kemik mineral yoğunluğunu değerlendirmek ve osteoporoz sıklığını saptamaktır. Çalışmada en iyi final boya ulaşmak ve bu hedefe ulaşırken kemik sağlığını bozmamak için "Hangi yaşta östrojen tedavisi başlanmalıdır?" sorusuna yanıt aranmıştır.Gereç ve Yöntem: İstanbul Bakırköy Kadın Doğum ve Çocuk Hastalıkları Eğitim ve Araştırma Hastanesi, Çocuk Endokrin ve Metabolizma Polikliniği'nden izlenmiş, yaşları 8,8 ile 28 yıl arasında değişen, Turner sendromu tanısı kromozom analizi ile kesinleştirilmiş, kemik metabolizması üzerine olumsuz etkisi olabilecek herhangi bir hastalığı bulunmayan 45 olgu çalışma grubuna dâhil edilmiştir. Bulgular: Düzeltilmiş vertebra z skoru östrojen başlama yaşı ile ters korelasyon gösteriyordu (p=0,042; r=- 0,550). Final boya ulaşan 10 olgudan 4'ünde osteoporoz görüldü. Osteoporoz görülen olguların ortalama vertebra z skoru -2,4 idi. Osteoporoz sınırında olmayan 6 olgunın vertebra z skoru ise < -1,3 idi. Osteoporoz görülen olguların ortalama östrojen başlangıç yaşı 14,95±2,18 yıl, osteoporoz görülmeyen olgularınki 14,48±1,67 yıl olarak saptandı (p=0,762). Final boyu 148 cm üzerine çıkan ve 148 cm altında kalan olgular karşılaştırıldığında 148 cm'nin üzerine çıkan olguların ortalama 15,61±1,10 yaşında, 148 cm altında kalan olguların 13,26±1,79 yaşında östrojen tedavisine başladıkları görüldü (p=0,05). Sonuç: Östrojen takviye tedavisine başlama yaşında gecikmenin beklendiği kadar kötü kemik mineral yoğunluğu değerlerine neden olmadığı saptandı.

Objective: Short stature and hypogonadism are the most common features of Turner syndrome related to hypogonadism. It is important to determine the optimal dose and the appropriate timing of estrogen replacement therapy in patients who must undergo estrogen replacement therapy because of ovarian insufficiency . The aim of this study was to evaluate bone mineral density and to determine the frequency of osteoporosis among patients with Turner syndrome. We also tried to find a response to the question, "At what age estrogen treatment should be started?" so as to reach optimal final height without impairing bone health.Material and Methods: Forty five patients with final diagnosis of Turner Syndrome based on chromosomal analysis who were followed up in the Outpatient Clinics of Pediatric Endocrinology, and Metabolism of Istanbul Bakırköy Maternity, and Children's Health and Diseases Training and Research Hospital whose ages ranged between 8.8, and 28 years without any other disease which could have a negative effect on bone metabolism were included in this study.Results: The corrected spine z-score was inversely correlated with the age of onset of estrogen therapy (p: 0,042, r: -0,550). Osteoporosis was detected in 4 of 10 patients who reached to their final height. Spine z score of 6 cases without osteoporosis was <= 1.3. The mean z-score of patients with osteoporosis was -2.4. Mean ages of onset of estrogen therapy age were 14.95±2.18, and 14.48±1.67 years among the patients with osteoporosis and without osteoporosis, respectively (p=0,762). When the patients with final heights longer, and shorter than 148 cm were compared, mean ages of onset of estrogen therapy were 15.61±1.10, and 13.26±1.79cm, among patients >148, and < 148 cm -tall, respectively (p=0,05). Conclusion: We determined that the delay in the estrogen replacement therapy does not lead to a dramatic decrease in bone mineral density as anticipated.
Frequency of osteoporosis in children with turner syndrome and determining the optimal age of the onset of estrogen replacement therapy
Keywords: Turner Sendromu; Östrojen Takviyesi; Osteoporoz; DEXA; Turner Syndrome; Estrogen Replacement Therapy; Estrogen Replacement Therapy; Osteoporosis; DEXA